BCM150: Biochemistry I / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2021)
This subject covers an introductory concept of basic biochemistry in the following topics: carbohydrate, fatty acids, enzymes, amino acids, proteins, nucleic acids and metabolism. This subject will be performed via face-to-face lecture discussion.